Advocacy Today, Advocacy Tomorrow, Advocacy Forever! - John Moorman (Virginia Libraries, 2009)
John Moorman is particularly well qualified to write about being an advocate for libraries. Since 1975, he has been the top library administrator of public libraries; a multi-type library system; and library systems in North Carolina, Texas, Illinois, and Virginia. Active in both state and national library organizations, he has served as Illinois American Library Association Chapter Councilor, president of the Small and Medium-Sized Libraries section of the Public Library Association, and has served several terms on the Board of Directors of the Public Library Association. Moorman is currently a member of the ALA Committee on the Status of Women in Librarianship, serves on the ALA Council as the representative of the Intellectual Freedom Round Table, and is vice president/ president-elect of the Virginia Library Association.